Low pressure DC-plasma system for the modification of polymeric membrane surfaces - Chalad Yuenyao,; Thawat Chittrakarn,; Yutthana Tirawanichakul,; Hideki Nakajima, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The main objectives of this work were to develop a lab-scale direct current (DC) glow discharges plasma system for modification of organic and inorganic membranes. Characteristics of plasma system were presented under the discharge of five gases (Ar, N2, air, O2, and CO2). A Langmuir double probe was used for the evaluation of the electron temperature (Te) and electron density (ne) of plasmas. The current and voltage (I-V) characteristic curves were analyzed. Relationships between breakdown voltage (VB) of gases and products of gas pressure and inter-electrode gap (pd) were studied in form of Paschen curves. The results showed that Te of plasma in various gases was in the range of 4-13 eV, while the ne varied between 108 and 109 cm-3. The plasma generated at different gas pressure and applied voltage is in the normal and abnormal modes. Finally, the constructed DC-plasma system was utilized for modification of polymeric membrane surfaces. Treatment time, discharge power and type of gas were varied. The tailoring of membrane surfaces was analyzed through the water contact angle and percent-weight loss (PWL) measurements, DMTA, AFM, XPS and FTIR spectrum. It could be shown that DC-plasma from this system can be used to modify the surface of polymeric membranes.